Implementing the Flipped Classroom Model in the Teaching of History - Siti Waznah Abdul Latif; Rohani Matzin; Rosmawijah Jawawi; Mar Aswandi Mahadi; Jainatul Halida Jaidin; Lawrence Mundia; Masitah Shahrill (Journal of Education and Learning (EduLearn), 2017)
This study investigated the effectiveness in implementing the Flipped Classroom model in teaching History and to identify the students’ perceptions using this approach towards their learning. The chosen History topic was on ‘James Brooke’s activities in Sarawak in the 1840s’. The sample consisted of twelve students from two Year 9 classes in one of the secondary schools in Brunei Darussalam. In adopting the Flipped Classroom approach, the students were required to watch a video lesson outside the classroom setting. To measure its effectiveness, a test instrument was used, and five students were interviewed. The findings revealed that the utilisation of this instructional method was effective in teaching History, as there were improvements in the students’ test results. The analyses of the students’ perceptions using this approach revealed that while some students believed that it helped them improve in their communication and writing skills, others did not perceive it effective for their learning.